Respuesta :
Answer:
Step-by-step explanation:
(2x-5)(3x+8)
6x^2-15x+16x-40
6x^2+x-40
(x^2+15x+65)+(6x^2+x-40)
7x^2+16x+25
Answer: B)
-----------------------------------
(4x+1)(3x-4)=12x^2+3x-16x-4=12x^2-13x-4
(12x^2-13x-4)-(5x^2-10x-12)=7x^2-3x+8
Answer: D)
------------------------
(3x+2)(x-5)=3x^2+2x-15x-10=3x^2-13x-10
(8x^2+19x+4)+(3x^2-13x-10)=11x^2+6x-6
Answer: A)
----------------------------
(6x+1)(3x-7)=18x^2+3x-42x-7=18x^2-39x-7
(18x^2-39x-7)-(7x^2-34x-20)
11x^2-5x+13
Answer: C)
7x²+16x+25 is corresponds to the equivalent expression of (x²+15x+65) + (2x - 5) (3x +8).
7x²-3x+8 is corresponds to the equivalent expression of (4x + 1)(3x - 4) - (5x²-10x-12)
11x²+6x-6 is corresponds to the equivalent expression of (8x²+19x+4) + (3x + 2)(x - 5).
11x²-5x+13 is corresponds to the equivalent expression of (6x + 1)(3x - 7) - (7x²-34x-20)
What is expression?
Expressions is the defined as mathematical statements that have a minimum of two terms containing variables or numbers.
Given expression no. 1 as :
⇒ (x²+15x+65) + (2x - 5) (3x +8).
⇒ x²+15x+65 + 6x²-15x+16x-40
⇒ 7x²+16x+25
Hence, the correct answer would be option (B).
Given expression no. 2 as :
⇒ (4x + 1)(3x - 4) - (5x²-10x-12)
⇒ 12x²+3x-16x-4 - 5x²+10x+12
⇒ 12x²-13x-4 - 5x²+10x+12
⇒ 7x²-3x+8
Hence, the correct answer would be option (D).
Given expression no. 3 as :
⇒ (8x²+19x+4) + (3x + 2)(x - 5).
⇒ (8x²+19x+4) + 3x²+2x-15x-10
⇒ 8x²+19x+4 + 3x²-13x-10
⇒ 11x²+6x-6
Hence, the correct answer would be option (A).
Given expression no. 4 as :
⇒ (6x + 1)(3x - 7) - (7x²-34x-20)
⇒ 18x²+3x-42x-7- 7x²+34x+20)
⇒ 11x²-5x+13
Hence, the correct answer would be option (C).
Learn more about Expressions here:
brainly.com/question/21751419
#SPJ2